2010
DOI: 10.3171/2009.6.jns081490
|View full text |Cite
|
Sign up to set email alerts
|

Risk profile associated with convexity meningioma resection in the modern neurosurgical era

Abstract: Object. Although meningiomas are commonly found along the supratentorial convexity, the risk profile associated with this subset of lesions in the modern neurosurgical era is unknown.Methods. The authors retrospectively reviewed the clinical course of patients with supratentorial convexity meningiomas treated during the past 10 years. All patients had undergone MR imaging within 72 hours after surgery and at least 1 year of clinical follow-up. Patients with multiple meningiomas, hemangiopericytomas, malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 30 publications
2
68
3
3
Order By: Relevance
“…Radiosurgery, and a growing propensity for observation of smaller me ningiomas, has inherently altered the profile of tumors undergoing resection at our center and others, because they are likely to be bigger and more aggressive that those operated on in the past. 16 Importantly, medialthird sphenoid wing meningio mas are most notable for their proximity to the ipsilateral optic nerve and optic apparatus, which is the symptom prompting the diagnostic imaging study in more than two-thirds of these cases. Optic canal invasion and CS involvement are frequent features of these tumors, and are more common than with lateral parasylvian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Radiosurgery, and a growing propensity for observation of smaller me ningiomas, has inherently altered the profile of tumors undergoing resection at our center and others, because they are likely to be bigger and more aggressive that those operated on in the past. 16 Importantly, medialthird sphenoid wing meningio mas are most notable for their proximity to the ipsilateral optic nerve and optic apparatus, which is the symptom prompting the diagnostic imaging study in more than two-thirds of these cases. Optic canal invasion and CS involvement are frequent features of these tumors, and are more common than with lateral parasylvian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it seems that aggressive removal of malignant meningiomas is associated with greater risk of neurological morbidity, regardless of extent of resection, than in lower-grade meningiomas (Table 5). 19 Furthermore, many of our worst complications with these cases occurred in patients who underwent GTR. Although there is little doubt of the desirability of GTR in cases in which there is a clear plane between the tumor and normal brain, nerves, or vessels, often such a plane does not exist with these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated an increased risk of higher grade meningiomas in the convexity location. 5,8,9,36,37 Fifth, the current study is limited to the population of the United States, which limits the ability to generalize the results to other countries that may have significantly different genetic and environmental factors. Sixth, we must acknowledge limitations in the collection of race and ethnicity data.…”
Section: Limitationsmentioning
confidence: 99%